Pengontrolan Kecepatan Aliran Vortex Berbasis Arduino Sebagai Metoda Pemisah Campuran Serbuk Tembaga dan Aluminium - Fico Trianda Ravelli; Firman Ridwan (METAL: Jurnal Sistem Mekanik dan Termal, 2019)
Several methods have been developed to separate gold from alluvial using the principle of density. Density is used as a basic concept in material separation. One of the supporting methods that can be used to utilize the vortex flow as a separation medium. With vortex flow, two materials of different density can be separated through lift force. This study aims to determine the effect of vortex flow velocity on its ability to separate two different types of density material. Aluminum and Copper powders are used as test materials with a powder size of 18-200 mesh. The tests are carried out with a variation of 10 flow rates with water as a fluid. The results showed that Aluminum and Copper can be optimally separated at the flow rate (165.25-167.77) ml/s. While for the most effective effectiveness of Al separation is the flow rate (163.22-168.87) ml / s and copper separation at the flow rate (83.5-85) ml/s.